REThinking the role of the RET oncogene in breast cancer - Di Grazia, Giuseppe; Conti, Chiara; Nucera, Sabrina; Motta, Gianmarco; Martorana, Federica; Stella, Stefania; Massimino, Michele; Giuliano, Mario; Vigneri, Paolo (Frontiers in Oncology, 2024)
The REarranged during Transfection (RET) receptor tyrosine kinase plays a crucial role in the development of various anatomical structures during embryogenesis and it is involved in many physiological cellular processes. This protein is also associated with the initiation of various cancer types, such as thyroid cancer, non-small cell lung cancer, and multiple endocrine neoplasms. In breast cancer, and especially in the estrogen receptor-positive (ER+) subtype, the activity of RET is of notable importance. Indeed, RET seems to be involved in tumor progression, resistance to therapies, and cellular proliferation. Nevertheless, the ways RET alterations could impact the prognosis of breast cancer and its response to treatment remain only partially elucidated. Several inhibitors of RET kinase have been developed thus far, with various degrees of selectivity towards RET inhibition. These molecules showed notable efficacy in the treatment of RET-driven tumors, including some breast cancer cases. Despite these encouraging results, further investigation is needed to fully understand the potential role RET inhibition in breast cancer. This review aims to recapitulate the existing evidence about the role of RET oncogene in breast cancer, from its pathogenic and potentially prognostic role, to the clinical applications of RET inhibitors.